Analysis of Students' Ability at SMP Negeri 1 Sigi in Solving Direct Proportion Problems Based on Learning Styles - Herawati Herawati; Mustamin Idris; Bakri M Bakri M; Fajriani Fajriani (FKIP - Universitas Riau, 2026)
Based on initial observations at SMP Negeri 1 Sigi, 65% of students had not reached the Minimum Mastery Criteria (KKM) due to difficulties in understanding word problems, performing cross-multiplication, and conventional teaching that overlooks diverse learning styles. This study aims to analyze students' mathematical problem-solving abilities on direct proportion topics from the perspective of Visual, Auditory, and Kinesthetic (VAK) learning styles. Employing a descriptive qualitative approach, data were collected using a VAK questionnaire, a written essay test structured around Polya’s four steps, and semi-structured interviews. Data were analyzed using the Miles and Huberman model and validated via member checking. The results revealed that the visual subject (MAS) fulfilled all Polya indicators systematically and comprehensively. The auditory subject (VAT) also met all indicators, demonstrating highly meticulous calculations. Conversely, the kinesthetic subject (MN) failed to complete the last two indicators for Problem 2 due to rushed and inaccurate multiplication operations. In conclusion, learning styles significantly influence students' problem-solving abilities, where visual students excel in comprehensive understanding, auditory students dominate in calculation precision, and kinesthetic students are constrained by a lack of meticulousness in abstract calculations.